the PENGGUNAAN METODE SIMPELKS DALAM MENGOPTIMALKAN PENDAPATAN PADA PENJUALAN MAKANAN DI RUMAH MAKAN DINDA BATUNIRWALA KECAMATAN TELUK MUTIARA - Damaris Lalang; Siti N. Aini Sya'ban; Dewi S. Penpada (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2021)
This research aims to optimize revenue on food sales at Dinda's restaurant and the use of available raw materials to generate optimal profits, so to determine the right combination to maximize profits, Linear Proggaming with the simplex method can be used. The results obtained by using the simplex method, namely the restaurant grinding Dinda should produce 17 portions of Chicken rice (X1), 44 portions of Fish rice (X2), 10 portions of Soto rice (X3). From the number of portions of food produced by Dinda's restaurant, she gets a daily profit of Rp. 1,250,000.